Highly stable and luminescent silica-coated perovskite quantum dots at nanoscale-particle level via nonpolar solvent synthesis - Gao, Fei; Yang, Weiqiang; Liu, Xiuling; Li, Yuanzheng; Liu, Weizhen; Xu, Haiyang; Liu, Yichun (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
[Display omitted] •Monodisperse CsPbBr3@SiO2 NCs are prepared by one-pot route in nonpolar solvents.•These NCs exhibit high photoluminescence quantum yield of 87%.•The core@shell NCs exhibit evidently improved stability compared to bare QDs.•LEDs with high CRI and efficiency are constructed with these CsPbX3@SiO2 NCs. Currently, unsatisfactory optical stability and toxicity of all-inorganic lead halide perovskite (CsPbX3, X  = Cl, Br, and I) quantum dots (QDs) with excellent photoelectric properties is a major obstacle for their practical application. In this work, the CsPbBr3 QDs were assembled into SiO2 shell via nonpolar solvent synthesis, and monodisperse CsPbBr3@SiO2 nanocomposites (NCs) with high photoluminescence quantum yield (PLQY) of ~87% were successfully prepared. Moreover, the introduced hydrophobic and multibranched trioctylphosphine oxide (TOPO) effectively suppressed the hydrolysis rate of tetraethoxysilane (TEOS), resulting in the formation of core@shell NCs at a nanoscale-particle level. Benefiting from the protection of TOPO and SiO2 shell, the CsPbBr3@SiO2 NCs exhibit remarkably improved stability against thermal treatment, UV irradiation and water compared to the bare perovskite-QDs. Notably, the anion-exchange reaction among different perovskite-QDs was completely inhibited. To improve stability of iodide-substituted perovskite-QDs and expand emission wavelength, the CsPbBr0.6I2.4@SiO2 NCs with PLQY of 75% were also successfully prepared by similar strategy. White light-emitting-diodes (WLEDs) were designed by combining CsPbBr3@SiO2 NCs with CsPbBr0.6I2.4@SiO2 NCs onto blue GaN chips. Bright white-light with high color-rendering index of 90 and luminous efficiency of 80 lm W−1 were achieved from these WLEDs, indicating the synthesized perovskite NCs possess huge potentiality in displays and solid-state lighting.